2015
DOI: 10.1002/pola.27632
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of asymmetrically superhydrophobic cotton fabrics via mist copolymerization of 2,2,2‐trifluoroethyl methacrylate

Abstract: We report here a simple strategy for fabricating asymmetrically superhydrophobic cotton fabric via a mist copolymerization of three monomers, 2,2,2‐trifluoroethyl methacrylate (TFMA), 2‐isocyanatoethyl methacrylate (IEM), and divinylbenzene (DVB). The copolymer layer on the cotton surface was confirmed by X‐ray photoelectron spectroscopy (XPS) analysis and attenuated total reflection (ATR) accessory, and the nanoscale hierarchical structures in the polymeric layer were demonstrated by observation of field emis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…The three monomers in the mist copolymerization play respective roles: DVB is used as a crosslinker; MA is designed to introduce ester groups to react with the hydroxyl groups of cellulose; and PBBA acts as the functional monomer to decrease the ammability of cotton fabric. Our previous works 45,46 reported that the diameters of the mist droplets range from 150 to 500 nm, and only a small number of the droplets (about 3%) is xed on the cotton surface during the mist feeding. Therefore, mist copolymerization generally results a thin polymeric layer on a single side surface of the substrate.…”
Section: Fabrication Of the Fr Cotton Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…The three monomers in the mist copolymerization play respective roles: DVB is used as a crosslinker; MA is designed to introduce ester groups to react with the hydroxyl groups of cellulose; and PBBA acts as the functional monomer to decrease the ammability of cotton fabric. Our previous works 45,46 reported that the diameters of the mist droplets range from 150 to 500 nm, and only a small number of the droplets (about 3%) is xed on the cotton surface during the mist feeding. Therefore, mist copolymerization generally results a thin polymeric layer on a single side surface of the substrate.…”
Section: Fabrication Of the Fr Cotton Surfacesmentioning
confidence: 99%
“…Asymmetrically superhydrophobic, 45,46 and wear-resistant 47 cotton fabrics were fabricated by feeding atomized monomer solutions to an in situ polymerization to build thin polymeric coatings on the cotton fabrics. The advantages of the mist polymerization include wider range of applicable monomers, tailorable coating thinness and surface morphology, simple operation, single faced modication, and almost no damage to the original properties of the fabric.…”
Section: Introductionmentioning
confidence: 99%
“…The original good vapor transmissibility and water adsorptivity of the opposite unmodified cotton side were inherited. 89 This can prevent mildew and extend the scope of cotton applications under moist conditions. Not only can the superhydrophobic surface possess a simple static waterproof function, but the more excellent superhydrophobic surfaces that can resist against the drop water impact have been also obtained via advanced methods.…”
Section: Waterproof Functionmentioning
confidence: 99%
“…The grafting method plays a significant role in fabricating a superhydrophobic surface with long-term stability owing to the relatively strong chemical bonding force. The grafting coating can be achieved through different procedures including solution immersion, 19,29 thermal treatment, 13 atomization, 89 and so on. Taking advantage of the grafting method, a large number of superhydrophobic surfaces have been prepared.…”
Section: Grafting Coatingmentioning
confidence: 99%
See 1 more Smart Citation